(3JhVjM GdJPcQI aj TQM GdJPcQIs - (3ddMSf Hf eMeO fXGe GdOjf GdfjSCHhQis; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYdfG ef GdeJacQjf ai Ndb GdCQV hGdSeGhGJ s
(3BNQgG (B:s
(3ZjQ hGVM s
(3ecJhHg HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B131 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B23 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B391s
Keywords: (3Gdadcs